Characteristics of the gas produced during biomass direct gasification in an autothermal pilot-scale bubbling fluidized bed reactor. (1st February 2017) - Pio, D.T.; Tarelho, L.A.C.; Matos, M.A.A.
Abstract: Direct (air) biomass gasification was demonstrated in a pilot-scale bubbling fluidized bed reactor and the influence of process parameters analyzed. For the operating conditions used, namely equivalence ratio between 0.17 and 0.36 and bed temperature between 700 and 850 °C, the process was demonstrated as autothermal and operating under steady-state. The dry gas produced shows the following composition (volumetric basis): 14.0–21.4% CO, 14.2–17.5% CO2, 3.6–5.8% CH4, 1.3–2.4% C2 H4, 2.0–12.7% H2 and 48.9–61.1% N2 . The lower heating value of the dry gas was between 4.4 and 6.9 MJ/Nm 3, with the highest values observed during the experiments with lower equivalence ratio. The specific dry gas production was between 1.2 and 2.2 Nm 3 /kg biomass (dry basis), the cold gas efficiency between 41.1 and 62.6% and the carbon conversion efficiency between 60 and 87.5%. The integrated analysis of new data from this study and a survey of published data shows that direct (air) biomass gasification produces gas mixtures with a wide range of variation in characteristics, that can be correlated with the biomass fuel properties and operating conditions used. Therefore, for each type of process application it is required specific experimental information to support an adequate scaling to the industrial scale. Highlights: Demonstration of direct biomass gasification in an 80 kWth bubbling fluidized bed. The direct gasification process supports autothermal and steady-state operation. Producer gas with LHV 4.4–6.9 MJ/Nm 3, in the upper range of literature values. Producer gas properties show a strong dependency on operating conditions. Gasification applications need to be supported by specific experimental information.